Perceived Barriers for Career Advancement Opportunities Among Local Managers in Japanese Subsidiaries in the Klang Valley - Chandran, Neela (2003)
This research empirically examines the extent to which perceived barriers to career advancement of local managers exists in Japanese subsidiaries in the Klang Valley. Japanese subsidiaries have a unique quality of high degree of centralization and this creates challenges when operating in a foreign country like Malaysia. These challenges create perceived barriers. Since these challenges are related to management directly, the local managers in Japanese subsidiaries are vulnerable to its influence. The perceived barriers in this study were examined through an analysis of 317 local managers working in 41 Japanese subsidiaries in the Klang Valley. Six main perceived barriers were tested: 1 ) Access to power and decision making authority 2) Opportunities for Promotion 3) Benefits and Wages 4) Performance Appraisal 5) Feedback and 6) Stereotype and Discrimination. The investigation was based on a quantitative method of data collection using a validated questionnaire. All the subsidiaries involved were from the manufacturing and non-manufacturing sector from the Klang Valley. Overall findings suggest that perceived barriers, as described in most literature, does indeed exist in Japanese subsidiaries in Malaysia and this hinders local managers career advancement opportunities. There is dualism between Japanese managers and local managers in terms of the way they are treated. Local managers' chances of promotion to higher positions are limited. This is due to an unofficial ceiling on promotion, preventing local managers from climbing to upper-level positions. By confirming many of the findings of research on perceived barriers of Japanese subsidiaries, especially in developing countries, this study demonstrates that while local managers are in the Japanese subsidiary, they have to work harder than their Japanese counterparts, to overcome the stereotype that local managers are too inferior to hold higher management positions.